THREE NEW SPECIES OF THE FAMILY CRICONEMOITIDAE (TAYLOR, 1936) THORNE, 1949 FROM MANIPUR - MOHILAL, N.; DHANACHAND, CH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1998)
Three new species of the family Criconemoitidae (Taylor, 1936) Thorne, 1949 are described and illustrated. Ogma (ogma) ornama n.sp. has a slightly ventrally curved body, the first annule discoid, larger than the corresponding body annules, robust stylet, body annules eighty in number, spermatheca spherical, vulva on the 13th annule from tail terminus. Anus on the 10th annule from tail terminus. Discocriconemella spermata n.sp. is distinctive in its long body, higher position of vulval opening, serrated annules, setoff spermatheca, slopping stylet knob. Criconemella ovospermata n.sp. differs from its closely related species in its smaller body, shape and length of tail, more posterior vulval opening, number of annules in body.